Quality deviation requirements in residential buildings: predictive modeling of the interaction between deviation and cause - Almusharraf, Abdullah Musharraf (Curtin University, 2015)
To address construction defects, sub-task requirements (STRs) were generated alongside a Bayesian belief network-BBN quantification, towards the modelling of a unique causation pattern. The study found that the patterns of direct causes of deviation from quality norms are unique for each STR, and that causation patterns cannot be generalised. The work conducted provides Building-Quality-Managers with a new visualization tool to clarify the STR-specific cause of quality deviation pathways when creating the built environment.